Morphological Study of Palatal Rugae in a Sudanese Population - Altayeb Abdalla Ahmed; Awrad Hamid (Hindawi Limited, 2015)
Palatal rugae patterns have unique characteristics and have been proposed as an alternative method to establish identity when other means, such as fingerprints and dental records, are not attainable. This study was conducted to determine the morphological characteristics of palatine rugae and to assess the existence of side asymmetry in them in Sudanese Arabs. It also assesses the possibility of determining sex using logistic regression. One hundred dental casts for 50 males and 50 females aged between 18 and 23 were studied for palatal rugae dimensions, shapes, and orientations, as well as sexual dimorphism and side symmetry. The most predominant rugae were primary, and the most prevalent shapes in both sexes were wavy, curved, and straight forms. The predominant orientation was forward. Side asymmetry existed more in the orientations than in the shapes, but no side asymmetry was recorded in the dimensions. There was no significant sexual dimorphism in the rugae dimensions, shapes, and orientations, except for forward-directed rugae (P<0.037). A predictive value of 60% was obtained in assigning sex using dimensions and orientations and of 58% using shapes alone. Therefore, the palatal rugae are not recommended for assigning sex effectively among Sudanese Arabs unless it is the only means available.